AN EXPERIMENTAL STUDY: DOES WATCHING A VIDEO CHANGE PERCEPTIONS? - Amber Baseer; Dr Elizabeth Schwaiger (International Journal of Contemporary Issues in Social Sciences, 2024)
The present research investigated the affect of stereotypes about veiling by means of a short video. Experimental strategy employing a within subject design was used to find out the change in perception regarding veiling of university students. The sample consisted of 98 participants with ages ranging from 17-28 years. The data was collected from a a liberal arts university of Lahore, Pakistan via systematic sampling. Students were given a measure of perceptions about women who veil pre- and post-watching a video about a compassionate Muslim woman. Findings of the study suggested that though these university students did not have negative stereotypes about women who veil, a 5-minute video still served as a means of changing their perception in a positive direction.